2011
DOI: 10.1164/rccm.201006-0937oc
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease and Long-Term Exposure to Traffic-related Air Pollution

Abstract: Long-term exposure to traffic-related air pollution may contribute to the development of COPD with possibly enhanced susceptibility in people with diabetes and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
190
2
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(216 citation statements)
references
References 37 publications
11
190
2
13
Order By: Relevance
“…Anthropogenic production of NO x is largely attributed to fossil fuel combustion, with the transportation sector accounting for 68 % of NO x emissions in Ontario during 2008 (MOE, 2011). Previous studies investigating the spatial distribution of NO x have focused on near-road environments as a means to assess human exposure to trafficrelated air pollution (TRAP), characterize TRAP dilution and chemical evolution, inform urban infrastructure planning and policy, and validate dispersion models (Villena et al, 2011;health effects associated with exposure to NO 2 when used as a marker for TRAP include the exacerbation of asthma symptoms, the increased risk of developing cardiovascular and lung diseases, and increased mortality rates (Andersen et al, 2011;Valari et al, 2011;Pereira et al, 2010;Jerrett et al, 2009;Salam et al, 2008, and references therein; Nafstad et al, 2003). Therefore, an effective means of monitoring the spatio-temporal behaviour of NO 2 could do much to support the development of appropriate pollution mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic production of NO x is largely attributed to fossil fuel combustion, with the transportation sector accounting for 68 % of NO x emissions in Ontario during 2008 (MOE, 2011). Previous studies investigating the spatial distribution of NO x have focused on near-road environments as a means to assess human exposure to trafficrelated air pollution (TRAP), characterize TRAP dilution and chemical evolution, inform urban infrastructure planning and policy, and validate dispersion models (Villena et al, 2011;health effects associated with exposure to NO 2 when used as a marker for TRAP include the exacerbation of asthma symptoms, the increased risk of developing cardiovascular and lung diseases, and increased mortality rates (Andersen et al, 2011;Valari et al, 2011;Pereira et al, 2010;Jerrett et al, 2009;Salam et al, 2008, and references therein; Nafstad et al, 2003). Therefore, an effective means of monitoring the spatio-temporal behaviour of NO 2 could do much to support the development of appropriate pollution mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, it is suggested that higher exposure to such hazards increases the mortality in COPD patients. 15,16 Similarly, in household works, inefficient cooking fuels and technologies produce high levels of household air pollution with a range of health-damaging pollutants, including small particles that penetrate deep into the lungs. 17 In consistent with our results, one of the studies illustrated greater exposures among women, who spend the most times near the domestic firewood.…”
mentioning
confidence: 99%
“…Air pollution is likely to be a factor leading to an increase in morbidity and mortality due to the effects of climate change in Australia [18] and there is a considerable amount of research indicating causation between general air pollution and a range of diseases [73] particularly chronic obstructive pulmonary disease resulting from traffic pollution [74]. We spend over 70% of our time in buildings [75] with little awareness as to how indoor environments may adversely affect public health, such as exposure to known factors of dust mites, endotoxins, mould passive smoke inhalation [75].…”
Section: Airtight Buildingsmentioning
confidence: 99%